1994
DOI: 10.1002/ar.1092400303
|View full text |Cite
|
Sign up to set email alerts
|

Type III collagen is a major component of interodontoblastic fibers of the developing mouse molar root

Abstract: This study presents for the first time, immunohistochemical observations which demonstrate the presence of IOF at least during root circumpulpal dentin formation and which reveal that type III collagen is a major component of IOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Furthermore, TEM micrographs revealed very weak positive labelling for III‐CF of the forming collagen fibrils throughout the entire pre‐dentine layer, until the mineralization front. This is only partially in accordance with the studies of Ohsaki & Nagata (1994) that showed a strong staining for III‐CF in interodontoblastic fibres of rat molars. In human developing teeth, Lukinmaa et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, TEM micrographs revealed very weak positive labelling for III‐CF of the forming collagen fibrils throughout the entire pre‐dentine layer, until the mineralization front. This is only partially in accordance with the studies of Ohsaki & Nagata (1994) that showed a strong staining for III‐CF in interodontoblastic fibres of rat molars. In human developing teeth, Lukinmaa et al.…”
Section: Discussionsupporting
confidence: 88%
“…Dentine is first deposited by the odontoblasts as a layer of non-mineralized organic matrix called pre-dentine that lines the innermost pulpal portion and that varies in thickness; however, it remains constant during ageing because the amount that calcifies is balanced by addition of newly-secreted matrix (Nanci 2003). The first sign of pre-dentine formation is the appearance of large-diameter collagen fibrils, called von Korff fibres, that appear at least during radicular circumpulpal dentine formation and mainly consist of type IIIcollagen fibrils (III-CF) (Ohsaki & Nagata 1994, Kitasako et al 2002. Although their existence Correspondence: Prof. Lorenzo Breschi, Division of Dental Sciences and Biomaterials, Department of Biomedicine, University of Trieste, Via Stuparich, 1, 34129 Trieste, Italy (Tel.…”
Section: Introductionmentioning
confidence: 99%
“…Type I collagen is found mainly in thick fibrils, whereas type III collagen occurs in thin fibrils in the liver, skin, and tendon (Nowack et al 1976;Fleischmajer et al 1981) and is scattered throughout the tissue of human dental pulp but not as fibrils passing between the odontoblasts (Magloire et al 1982). However, investigations of the developing mouse molar have revealed collagen type III as a major component of interodontoblastic fibers (Shroff and Thomas 1992;Ohsaki and Nagata 1994). Our study has demonstrated the presence of collagen type III in the predentin layer but not as a component of the interodontoblastic fibers of the teeth examined.…”
Section: Discussionmentioning
confidence: 96%
“…The von Korff fibers have been frequently reported in mantle dentin . These fibers consist of coarse, bundled collagen fibrils of type III, with a minor portion of type I , and run with their long axis parallel to that of the odontoblast processes . Mantle dentin is also different in biochemical composition : for example, it seems to be absent of phosphoproteins .…”
Section: Mantle Dentinmentioning
confidence: 99%